1991
DOI: 10.1242/jcs.99.3.523
|View full text |Cite
|
Sign up to set email alerts
|

Telophase disc: a new mammalian mitotic organelle that bisects telophase cells with a possible function in cytokinesis

Abstract: We have discovered a novel mitosis-specific human autoantigen that arises at the centromeres of prophase chromosomes, but ultimately participates in formation of an organelle that bisects the cell at late anaphase and during telophase. The organelle, discernible as a three-dimensional disc by confocal microscopy, encompasses the entire midzone diameter, and its distribution survives disassembly of interpolar microtubules by cold temperature treatment and detergent lysis of cells. Cytokinetic furrow contraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…We and other groups found that RCC2 localized at the midbody during cytokinesis (Fig. 3p-r) 35 . However, whether RCC2 plays a role in cytokinesis is largely unknown.…”
Section: Rcc2 Is Involved In the Regulation Of Cytokinesis In Nudcl2 ...mentioning
confidence: 51%
See 3 more Smart Citations
“…We and other groups found that RCC2 localized at the midbody during cytokinesis (Fig. 3p-r) 35 . However, whether RCC2 plays a role in cytokinesis is largely unknown.…”
Section: Rcc2 Is Involved In the Regulation Of Cytokinesis In Nudcl2 ...mentioning
confidence: 51%
“…RCC2, also known as telophase disc protein of 60 kDa (TD-60), was reported to take part in spindle assembly and cell migration [35][36][37][38][39] . We and other groups found that RCC2 localized at the midbody during cytokinesis (Fig.…”
Section: Rcc2 Is Involved In the Regulation Of Cytokinesis In Nudcl2 ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Regulator of chromosome condensation 2 (RCC2), also known as telophase disc-60 (TD60), was initially identified in the anaphase spindle midzone (1). RCC2 is an essential protein in the chromosomal passenger complex (2).…”
Section: Introductionmentioning
confidence: 99%